Direct Binding of the pH-Regulated Protein 1 (Pra1) from Candida albicans Inhibits Cytokine Secretion by Mouse CD4+ T Cells - Bergfeld, Arne; Dasari, Prasad; Werner, Sandra; Hughes, Timothy R.; Song, Wen-Chao; Hortschansky, Peter; Brakhage, Axel A.; Hünig, Thomas; Zipfel, Peter F.; Beyersdorf, Niklas (Frontiers in Microbiology, 2017)
Opportunistic infections with the saprophytic yeast Candida albicans are a major cause of morbidity in immunocompromised patients. While the interaction of cells and molecules of innate immunity with C. albicans has been studied to great depth, comparatively little is known about the modulation of adaptive immunity by C. albicans. In particular, direct interaction of proteins secreted by C. albicans with CD4+ T cells has not been studied in detail. In a first screening approach, we identified the pH-regulated antigen 1 (Pra1) as a molecule capable of directly binding to mouse CD4+ T cells in vitro. Binding of Pra1 to the T cell surface was enhanced by extracellular Zn2+ ions which Pra1 is known to scavenge from the host in order to supply the fungus with Zn2+. In vitro stimulation assays using highly purified mouse CD4+ T cells showed that Pra1 increased proliferation of CD4+ T cells in the presence of plate-bound anti-CD3 monoclonal antibody. In contrast, secretion of effector cytokines such as IFNγ and TNF by CD4+ T cells upon anti-CD3/ anti-CD28 mAb as well as cognate antigen stimulation was reduced in the presence of Pra1. By secreting Pra1 C. albicans, thus, directly modulates and partially controls CD4+ T cell responses as shown in our in vitro assays.